Zinc phosphate-based nanoparticles as alternatives to zinc oxide in diet of weaned piglets - Kociova, Silvia; Dolezelikova, Kristyna; Horky, Pavel; Skalickova, Sylvie; Baholet, Daria; Bozdechova, Lucie; Vaclavkova, Eva; Belkova, Jaroslava; Nevrkla, Pavel; Skladanka, Jiri; Do, Tomas; Zitka, Ondrej; et al. (Journal of animal science and biotechnology, 2020)
BACKGROUND: The high doses of zinc oxide (ZnO) administered orally to piglets for the prevention of diarrhea and increase of growth rate can contaminate pig farms and the surrounding environment. Therefore, there is a need to find a replacement of high doses of dietary ZnO with an equally effective alternative. In the present study, the effect of two formulations of zinc phosphate-based nanoparticles (ZnA and ZnC NPs) on growth performance, intestinal microbiota, antioxidant status, and intestinal and liver morphology was evaluated. A total of 100 weaned piglets were randomly divided into 10 equal groups with the base diet (control) or the base diet supplemented with ZnA, ZnC, or ZnO at concentrations 500, 1000, and 2000 mg Zn per kilogram of diet. Supplements were given to animals for 10 days. Fecal samples were collected on day 0, 5, 10 and 20. At the end of the treatment (day 10), three piglets from each group were sacrificed and analyzed. RESULTS: Comparing to that of control, the significantly higher piglet weight gain was observed in all piglet groups fed with ZnA (P < 0.05). Differences in the total aerobic bacteria and coliform counts in piglet feces after NPs supplementation compared to that of control and ZnO groups were also found (P < 0.05). The majority of aerobic culturable bacteria from the feces represented Escherichia (28.57-47.62%), Enterococcus (3.85-35.71%), and Streptococcus (3.70-42.31%) spp. A total of 542 Escherichia coli isolates were screened for the virulence genes STa, STb, Stx2, F4, and F18. The substantial occurrence of E. coli virulence factors was found on day 5, mainly in fimbrillary antigen and thermostable toxins, except for piglets fed by ZnC. Zn treatment decreased Zn blood levels in piglets fed with ZnO and ZnA (500 mg/kg) and increased in ZnC (2000 mg/kg) compared to that of control (P < 0.05). The antioxidant status of piglets was affected only by ZnA. While some changes in the liver and the intestinal morphology of piglets with NPs were observed, none were serious as reflected by the normal health status and increased weigh gain performance. CONCLUSIONS: Our results indicate that ZnA NPs have a positive effect on the piglet growth performance even at the lowest concentration. The prevalence of E. coli virulence factors was lowest in pigs supplemented with ZnC. Zinc phosphate-based nanoparticles may be an effective alternative to ZnO.
Keywords: E. coli STa, STb, Stx2, F4, F18; Fecal coliforms; Diet; Microbiota; Antioxidant status